2006
DOI: 10.1093/ajcn/84.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of protein and leucine stimulates muscle protein synthesis rates to the same extent in young and elderly lean men

Abstract: Co-ingestion of protein and leucine with carbohydrate after activities of daily living improves whole-body protein balance, and the increase in muscle protein synthesis rates is not significantly different between lean young and elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
122
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 33 publications
11
122
0
12
Order By: Relevance
“…our data on the effect of leucine on skeletal muscle mass support the findings of studies in healthy human volunteers which show that leucine can have a net anabolic effect on skeletal-muscle protein synthesis in young (37) and elderly men (38)(39)(40). It also supports the finding in diabetic and somatostatin-treated fasted rats that leucine stimulates signaling pathways, leading to protein translation through insulin-dependent and insulin-independent pathways (14,15).…”
Section: Discussionsupporting
confidence: 88%
“…our data on the effect of leucine on skeletal muscle mass support the findings of studies in healthy human volunteers which show that leucine can have a net anabolic effect on skeletal-muscle protein synthesis in young (37) and elderly men (38)(39)(40). It also supports the finding in diabetic and somatostatin-treated fasted rats that leucine stimulates signaling pathways, leading to protein translation through insulin-dependent and insulin-independent pathways (14,15).…”
Section: Discussionsupporting
confidence: 88%
“…These data are supported by the observation that leucine increased protein synthesis in pregnant tumour-bearing rats, possibly resulting from changes in the ubiquitin -proteasome system (Ventrucci et al, 2004). In humans, leucine supplementation resulted in an improved muscle protein synthesis in young (Koopman et al, 2005) and elderly volunteers (Katsanos et al, 2006;Koopman et al, 2006;Rieu et al, 2006). There are two clinical trials in cancer patients that studied oral BCAA supplementation after surgical removal of the tumour.…”
mentioning
confidence: 85%
“…However, combined ingestion of carbohydrate and protein during recovery from physical activity resulted in similar increases in mixed muscle protein synthesis rates, measured over a 6-h period, in young and elderly men (96) . Consistent with our findings, Drummond et al (61) reported similar post-exercise muscle protein synthesis rates over a 5-h recovery period in young v. elderly subjects following the ingestion of carbohydrate with an EAA mixture.…”
Section: Ageing and The Anabolic Response To Combined Exercise And Numentioning
confidence: 74%